Stem Cell Delivery of Oncolytic Adenovirus DNX-2401 Following Surgical Resection for the Treatment of Glioblastoma in a Murine Model. (1st September 2019) - Gopakumar, Sricharan; Gumin, Joy; Daou, Marc; Ledbetter, Daniel; Kerrigan, Brittany Parker; Lang, Frederick F
Abstract: INTRODUCTION: Current treatments for glioblastoma (GBM) are minimally effective and the prognosis for patients is uniformly poor despite multimodal therapy. While prior studies have examined intratumoral injection of oncolytic virus DNX-2401 into recurrent tumor, the potential of DNX-2401 delivered into the surgical resection cavity using tumor-tropic human mesenchymal stem cells (MSCs) has not been evaluated. We hypothesize that using a fibrin scaffold for transplanting MSCs loaded with DNX-2401 (MSCs-DNX-2401) into the resection cavity will improve MSC and viral delivery, kill residual tumor cells, decrease GBM recurrence, and improve overall survival. METHODS: MSCs-DNX-2401 were either seeded in fibrin or suspended in PBS and placed in the upper wells of a transwell with U87 tumor cells plated below. After 1 wk, U87 cells were counted to compare rates of cellular killing to evaluate release of DNX-2401 from fibrin-seeded MSCs. U87 tumor cells were then transduced with mCherry-Luciferase and implanted in 20 mice. Fluorescence-guided surgical resection of glioma xenografts was performed on day 10. Either MSCs (control) or MSCs-DNX-2401 (treatment) were seeded in fibrin and implanted in the resection cavity. Postoperative bioluminescence imaging was used to evaluate extent of residual disease and weekly serial imaging was used to monitor tumor recurrence in each group. RESULTS: Transwell experiments demonstrate significant cytotoxic killing of U87 tumor cells with MSCs-DNX-2401 seeded in fibrin having comparable oncolytic activity to MSC-DNX-2401 without fibrin. In vivo studies show four mice in the treatment group (40%) demonstrating complete responses to delivery of MSCs-DNX-2401 using fibrin. Kaplan-Meier survival analysis demonstrates survival benefit with prolonged median and overall survival in the treatment group ( P  < .05). CONCLUSION: This translational study validates the overall treatment paradigm for delivering oncolytic virotherapy into the tumor resection cavity using MSCs seeded in fibrin to decrease tumor recurrence and prolong overall survival. This project represents an important preliminary step for eventual application of this technology in human patients.